CBCT imaging of extensive nasopalatine duct cyst :Case report - Muhammed Sümbüllü; Osman Bilge; Ummuhan Tozoglu (Cumhuriyet University, 2013)
The nasopalatine duct cyst (incisive canal cyst) (NPDC) is the most common non-odontogenic cyst in the oral cacity, occuring approximately 1% of the population. It is an uncommon condition that generally occurs in the maxillofacial bones. This lesion may be clinically silent for years without any symptoms. On examination, painless swelling, which was tender and fluctuant, was confirmed in the midline of his anterior hard palate. The overlying mucosa appeared normal in color. We performed CBCT to better identify lesion.This case demonstrates the typical clinical and radiographical features of a NPDC. CBCT can provide high-resolution images, short scanning time, and reduced radiation dose. CBCT therefore provides the opportunity for multiplanar imaging and three-dimensional (3D) information.